(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Aphorisms represent a significant linguocultural phenomenon, reflecting the collective worldview, values, and cultural priorities of a speech community. Through concise and expressive language, aphorisms encode national mentality, moral principles, and sociocultural experience. This article explores the linguocultural value expressed in English and Uzbek aphorisms by analyzing their semantic, stylistic, and cultural components. The study highlights how aphorisms function as carriers of cultural memory and demonstrates both universal and culture-specific features in English and Uzbek linguistic traditions.